Development of constitutional principles in the field of economic regulation - Naletov, Kirill I.; Kurbanov, Rashad A. (Journal of the Belarusian State University. Law, 2020)
Present paper is dedicated to the very basic modern trends of the legislative development of the provisions of Russian Constitution of 1993 on the state regulation of economy and the practice of their application by courts. The authors have chosen the principles of the division of state powers and duties of the state bodies of different levels; the independence of local self-government from the state power and the principle of limitation of liberty of commercial entities by rights and interests of other persons as the target of his research.